Penguatan Dukungan Pemerintah terhadap Badan Usaha Milik Desa (BUMDes) dalam Meningkatkan Kesejahteraan Masyarakat: Analisis Normatif terhadap Peraturan Pemerintah Nomor 11 Tahun 2021 - Misno; Sukarna (STIT Sirojul Falah Bogor, 2025)
This study aims to normatively and juridically analyze government support for Village-Owned Enterprises (BUMDes), assess its conformity with the principles of the welfare state, and formulate an ideal model for strengthening support following the establishment of BUMDes as legal entities through Government Regulation (PP) Number 11 of 2021. Employing a normative legal research approach with a focus on statute analysis and the welfare state theory, the study finds that the government support norms in PP 11/2021 remain general and lack detail, leading to legal uncertainty and regulatory disharmony concerning capital provision, guidance, and business facilitation. These normative gaps hinder BUMDes from optimizing their role as a welfare state instrument. Therefore, the research recommends an ideal model for strengthening support based on the principles of legal certainty, justice, and effectiveness, urging the government to promptly formulate more operational and detailed derivative regulations, and to achieve total synchronization of regulations across all levels of government.